What is
y

2
=

3
(
x

7
)
y−2=−3(x−7)y, minus, 2, equals, minus, 3, left parenthesis, x, minus, 7, right parenthesis written in standard form?

Respuesta :

Answer:

Standard form of the equation is:

∴ [tex]3x+y=23[/tex]

Step-by-step explanation:

Given equation:

[tex]y-2=-3(x-7)[/tex]

To convert the given equation to standard form of equation:

[tex]A(x)+B(y)=c[/tex]

Using distribution.

[tex]y-2=(-3x)+(-3\times-7)[/tex]

[tex]y-2=-3x+21[/tex]

Adding 2 both sides.

[tex]y-2+2=-3x+21+2[/tex]

[tex]y=-3x+23[/tex]

Adding [tex]3x[/tex] to both sides.

[tex]3x+y=3x-3x+23[/tex]

∴ [tex]3x+y=23[/tex]